KEKERASAN VERBAL BAHASA INDONESIA DALAM WACANA PASAR TRADISIONAL DI KOTA DENPASAR - Ambarwati, Nina (Humanis, 2013)
The research is backed by the language in usage by the precence of comunities that may give rice to  conflicts social. In addition, the research is also backed by the persence of community complaints that many people feel unconfortable due to the literary situation while shopping at traditional markets. Issues raised in this study were (1) how the form of verbal violence in the traditional market Town of Denpasar; (2) based on it’s meaning, what were the types of verbal violence that occurred in the traditional market Town of Denpasar; (3) what were the factors that affect the occurrence of verbal violence in the traditional market Town of Denpasar. The theory used in this research is the Searle’s theory of speech acts, Dell Hymes’s theory of speech events, Grice’s theory of implikatur, and the Pateda’s theory of language usage. Methods and techniques in this research consist of theree, namely 1) method and technique of data collection is the method “simak bebas libat cakap”; 2) method and tecnique of analysis data is a method of meaning interpretation; and 3) method and tecnique of presentation is an informal method of analysis results. The results obtained from ths reaserch is (1) verbal violence in the speech acts: asertif, directive, komisif, and declaration; (2) types of verbal violence that occur in the  traditional markets Town of Denpasar: invective, insults, threast, accusations, duress, satire, protest, suspicion, rejection, decision, greetings, and lies; and (3) factors that affect the occurrence of verbal violence: factor in the desire to convey something, moods, situations,circumstances, environment, and social level.
Keywords: verbal violence, implikatur, language usage.